Modification of ICHTJ sol gel process for preparation of medium sized ceramic spheres (Ø<100 µm). Issue 10 (December 2015) - Brykała, Marcin; Deptuła, Andrzej; Rogowski, Marcin; Łada, Wiesława
Abstract: In the Sol–Gel Laboratory at the Institute of Nuclear Chemistry and Technology (INCT), studies of synthesis of various advanced ceramic materials by the sol–gel method have been carried out for 50 years. The ceramics products, such as metal oxides, homogeneous mixtures of metal oxides, cermetals and metals, were obtained in various shapes, as irregular powders, monoliths, coatings, fibers or spherical particles with various diameters. A new method using a water-in-oil technique – the ICHTJ Process (INCT in English) was elaborated to synthesize spherical particles of metal oxide or mixture of metal oxides, with diameters below 100 µm. Through years, the method has been evaluated and optimized. Prepared sol solutions of metal cations are emulsified in 2-ethylhexanol-1 containing 1 volume % of the surfactant sorbitol monooleate. Drops of emulsion are gelled by extracting their water with this organic solvent. The main parameters e.g. flow rate; gelation time, syringe, sol solution etc. that have a strong influence on the optimization of the synthesis method and features of the spherical particles are described in this article through an example of synthesis of uranium oxycarbide – mixture of uranium dioxide with uranium carbide.